TÜRK TAEKWONDO MİLLİ TAKIM SPORCULARININ SEÇİLEN BAZI FİZİKSEL VE FİZYOLOJİK ÖZELLİKLERİNİN ANALİZİ - TEL, MİKAİL (Fırat Üniveristesi, 1996)
The purpose of this study was to measure and analyse; some selected physical and physiological charecteristics of Turkish national level Taekvvpndo sportmans. Measured variables, compeared between the Taekwondo sportmans who made the national team and who couldn't make the teams. And also, results compeared with some research results belong sportman and sedentary persons. The subjects in this study vvere 25 male Taekvvondo players who were invited to the national camp in 1995. 18 different physical and physiologial parameters were measured and analysed. The " t " test statistic was used to compare the datas. To determine the signifıcance of the differrences 0.05 confidance level was used. The results blongs Taekvvondo sportmen vvere following: For ali Taekwondo sportmans, mean sport ages was 10.80 ± 3.06, the mean age was 22.4 ± 2.9, the mean height was 177.4 ± 0.5 cm, the mean vveight was 66.6 ±11.1 kg, the mean percent body fat was 7.66 the mean resting heart- rate vvas 58.96 ± 6.08 beat/min, the mean systolic and diastolic blood perssure vvere 110.40 ± 8.88 and 66.40 ±10.36 mm/hg, the mean aerobic power was 49.89 ± 2.98 mUkg/min, the mean anaerobic power vvas 133.81 ±9.72 kg/m/sec, the mean sit and reach flexibility was 34.44 ± 5.31 cm, the mean grip strength vvere 47.30. ± 5.84 kg for right hand and 46.17 ± 5.66 kg for left hand, the mean leg strengt vvas 151.46 ± 25.31 kg, the mean back strengt vvas 151.74 ± 23.71 kg and the mean vital capacity vvas 4.73 ± 0.55 it. The values of the national team Taekvvondo sportmen vvere higher then some research results blong sedantary persons. Measured characteristics of Taekvvondo sportmen vvere similar the values of some sportmens who make individual and combat sports. in the resiing heart rate, systolic and diastolic pressure variables, there were signifıcant differenes betwen the Taekvvondo practitioners who made the team and who couldn't make the team. There vvere no significant differences in height, vveight, percent body fat, aerobic and anaerobic power, flexibility, grip- leg-bag strengt and respiration parameters betvveen groups.in conclusion, from this reseach results; İn the succes of Taekvvondo sport the physical and physiologial characteristics are important, but not only effecting factors to it.
The physical and physiological profile of Turkish national level taekwondo sportmens
Keywords: Spor; Sports